2020
DOI: 10.1016/j.tmp.2020.100752
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of international tourist flows from 1995 to 2018: A network analysis perspective

Abstract: Tourist arrivals and tourism revenues have been extensively studied to evaluate international tourist flows, whereas the structure and evolution of these flows have received less attention. Based on international tourist arrival data from 221 countries/regions during the period 1995–2018, this study applies network analysis to explore the structure and evolution of international tourist flows, and the roles and functions of countries/regions in the international tourist flow network. The results of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 55 publications
(113 reference statements)
0
37
0
Order By: Relevance
“…It provides algebraic analysis and visual expression of social relations [ 83 ], and has become a popular interdisciplinary academic method [ 84 ]. At present, the social network analysis method has been widely used in many fields such as tourism flow [ 85 , 86 ], energy consumption [ 87 , 88 ], environmental protection [ 89 , 90 ]. In this paper, the tourism eco-efficiency network is abstracted as a social network.…”
Section: Methodsmentioning
confidence: 99%
“…It provides algebraic analysis and visual expression of social relations [ 83 ], and has become a popular interdisciplinary academic method [ 84 ]. At present, the social network analysis method has been widely used in many fields such as tourism flow [ 85 , 86 ], energy consumption [ 87 , 88 ], environmental protection [ 89 , 90 ]. In this paper, the tourism eco-efficiency network is abstracted as a social network.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lozano and Gutierrez (2018) analyzed the structure and interaction between tourist sources and destinations in the global tourism network using the SNA method [12]. Shao et al (2020) applied SNA to discuss the structural characteristics and evolution rules of international tourism flow networks, as well as the roles and functions of various destinations in international tourism flow networks [13]. Wang et al (2021) believe that the spatial movement of tourists from source to destination, and between destinations, contributes to a regional tourism cooperation network, and they used SNA to analyze the structure of tourism scenic spot cooperation networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism flows will also promote the economic development of destinations, provide support for the construction and renovation of infrastructure and the promotion of tourism image of destinations, which in turn will attract more tourism flow. Shao et al, analyzed the influencing factors of international tourism flow and found that safety concerns, transportation accessibility or small populations had a strong impact on inbound tourism flow in Africa [13]. In addition, other factors such as the global and national economic situation and public health events represented by COVID-19 will also have an impact on tourism flows [13,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, international tourist arrivals reached 1.5 billion thanks to a decade of uninterrupted growth, and accounted for 10.3% of global GDP, generating 330 million jobs. By 2020, with the outbreak of COVID-19, tourism activities were forced to come to an abrupt halt and enter a deep economic crisis [3,4]. Due to global border closures, tourism has been one of the sectors most affected by the coronavirus pandemic [5].…”
Section: Introductionmentioning
confidence: 99%